Social and Economic Activities between Traders and Batik Suppliers in Klewer Market Surakarta - Yustitisia Biankum Dianono; Riadi Syafutra Siregar; Nurhadi Nurhadi (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
Klewer Market is one of the largest and most famous traditional markets in the city of Surakarta which sells and sells batik merchandise. This research examines the social phenomena that occur in trading activities between traders and batik suppliers at Klewer Market, Surakarta. Trading activities in traditional markets are subject to influencing social factors. The research method used is qualitative with an ethnographic approach. Data were collected through ethnographic interviews and non-participant observation with 7 informants (6 traders and 1 Head of Klewer Market). The research results show that in trading activities between traders and batik suppliers or wholesalers, there is a phenomenon of subscriptions that are built because of a sense of trust in each other. The subscription phenomenon makes it easier to ensure the supply of merchandise for traders and the accounts receivable system.